Grupo reflexivo com homens autores de violência e a aplicação do instituto da suspensão condicional do processo: uma análise a partir da atuação da vara de violência doméstica e familiar contra a mulher em Mossoró-RN - Rodrigues, Juliane (Universidade Federal Rural do Semi-Árido, 2019)
Data released on domestic and family violence against women in Brazil reveal that the rates remain high and unchanged. It is stipulated that, every 10 women, about 3 suffer violence. The absence of adaptation of the specific legal provisions to the activity of official bodies, is still one of the great obstacles to the fight against violence against women. In this context, the study presented here intends to make some considerations about the judicial activity regarding the implementation of mechanisms provided for in the Maria da Penha Law, which can be effective in preventing and coping with the current scenario of violence against women. In a special way, this study proposal aims to analyze the treatment of the aggressor from the formation of reflexive groups with men authors of violence against women in the judicial scope of the Specialized Varas, in order to understand the application of this measure and the reflexes procedural suspension from the application of the institution of the conditional suspension of proceedings. In this sense, to contextualize the reality of domestic and family violence against women, data from the main reports of national entities will be verified, in order to outline a social panorama of the current scenario of violence against women. On the other hand, based on the interpretation of the provisions of Law No. 11.340 / 2006, regarding the treatment of the aggressor, as well as, together with other legal instruments, the main innovations and obstacles to correct application of the Maria da Penha Law. To do so, in order to develop a closer to the local reality, data were collected and analyzed, from the application of semi-structured interviews with the coordinator of the reflexive group and the judge of the Domestic and Family Violence against the woman, located in the city of Mossoró-RN, as well as participation in suspension hearings. In this way, the research will evaluate the treatment measure of the agent of the aggression, from its inclusion in the reflexive groups and the procedural-criminal effects resulting from the application of the conditional suspension institute.
Artigo Acadêmico
Keywords: Suspensão condicional do processo; grupos reflexivos com homens autores de violência; Vara de violência doméstica e familiar contra a mulher em Mossoró-RN; Conditional suspension of the process; reflexive groups with male perpetrators of violence; Domestic violence and family violence against women in Mossoró-RN; CIENCIAS SOCIAIS APLICADAS::DIREITO